Safflower yellow reduces DEN-induced hepatocellular carcinoma by enhancing liver immune infiltration through promotion of collagen degradation and modulation of gut microbiota. Issue 21 (29th September 2021) - Fu, Huiying; Liu, Xia; Jin, Lu; Lang, Jiali; Hu, Zhiming; Mao, Wen; Cheng, Changpei; Shou, Qiyang
Abstract : SY exhibited a potent effect on the development of HCC by enhancing liver immune infiltration by promoting collagen degradation and modulating gut microbiota. Abstract : Safflower yellow (SY) is the main active ingredient isolated from the traditional Chinese medicine Carthamus tinctorius, which is a valuable natural edible pigment that is widely used to treat cerebrovascular and cardiovascular diseases. However, the effect of SY on hepatocellular carcinoma (HCC) remains unclear. In this study, we showed that SY decreased the degree of injury and inhibited the release of inflammatory factors in the liver of a diethylnitrosamine (DEN)-induced HCC mouse model. Flow cytometry and immunoblotting showed that SY increased the infiltration of CD8 + T cells and Gr-1 + macrophages to improve the immune microenvironment by affecting the expression of collagen fibers. Further cellular experiments showed that SY degraded the collagens in the liver cells through the TGF-β/Smad signalling pathway. SY also regulated the gut microbiota which may contribute to the immune microenvironment. In conclusion, SY exhibited a potent effect on the development of HCC by enhancing liver immune infiltration by promoting collagen degradation and modulating the gut microbiota. This study provides novel insights into the mechanism of SY as a candidate for the treatment of HCC in the future.